World’s First Nanorod Solar Module: Materials Fancy Goes Reality! - Rajan, Jose (2016)
For many years, solar cells had been considered as an inferior energy technology due to high cost – even in the renewable energy paradigm; however, progress in materials processing and engineering have helped them emerge as a frontline renewable energy technology with energy payback time that has been lowered from over a decade to a couple of years (at least in some parts of the world) during the last ten years. Commercial solar panels are typically manufactured on rigid platforms; fabricating them on flexible substrates, such as transparent plastics and metallic foils, would enable effective harvesting of energy in a number of diverse areas from indoor electronics to automobiles and from windows to portable applications. Furthermore, it would open up web-based roll-to-roll fabrication conducive to massive throughputs. Solution processable solar cells offer promising opportunities towards this end.